Mechanisms of action of Sri Lankan herbal medicines used in the treatment of diabetes: A review - Samarakoon, D.N.A.W; Uluwaduge, D.I; Siriwardhene, M.A (Journal of Integrative Medicine, 2019)
Natural plant-based remedies for diabetes mellitus have been proven to be safe and effective alternatives to Western medications, and details about more than 400 plants are available in the literature. Sri Lanka is a tropical country which is blessed with many natural plant products that can be utilized for the treatment of diabetes. But the knowledge of these plant-derived remedies, especially their doses, mechanism of action and toxicity has not been extensively researched. Therefore, this review focuses on documenting the plant-based remedies that the Sri Lankan Aurvedic physicians use and the extent of research that has been carried out on each of these plant-based remedies.
Keywords: Antidiabetic Diabetes mellitus Antioxidant Mechanism Natural plants Review